Empowerment Of Position And Roles Of Traditional Leaders In The Development Of Livestock Hamlet In The Banten Province - Kedi Suradisastra; D. Priyanto (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2011)
Developing livestock village is a suitable effort to enhance meat production for fulfilling increasing of the product demand. Developing livestock village in form of Sheep Hamlet in the Regency of Pandeglang, Province of Banten, is also function as forest and environmental buffer zone. Another target of such a livestock development center is to improve farmer’s income by at least 50% of Banten’s Minimum Regional Wage. The success of Sheep Hamlet so far depends upon the following socio-cultural factors: (a) the basic culture of the Bantams, (b) local leadership, and (c) decision making pattern and process. The development of livestock hamlet depends on the roles of local informal figure in the respective area. Such a local leader can help accelerating the success of a livestock development in a sustainable fashion. The existence of a respected local figure is a crucial entry point in the process of livestock hamlet development in the such area. Key words: Livestock hamlet, local institution